Surface integrity assessment of M3 HSS cutting taps after grinding at various machining conditions - Vendrame, Saimon [UNESP]; Silva, Rosemar Batista da; Machado, Alisson Rocha; Bianchi, Eduardo Carlos [UNESP]; Aguiar, Paulo Roberto [UNESP]; Baptista, Fabricio Guimaraes; Angelo Sanchez, Luiz Eduardo de [UNESP]; Jackson, Mark J. (Springer, 2018)
Grinding is a machining process that provides a combination of good surface finishing and tight dimensional tolerances on a machined component. Owing to these characteristics, it is employed in the finishing process of hardened parts, such as high-speed steel (HSS) cutting tools (principally drills and taps). Despite the various benefits, the specific energy in grinding is very high, resulting in high heat generated in the wheel-workpiece interface that could lead to thermal damages. To avoid such problems, aiming to maximize productivity and preserve the integrity of the machined component, a cutting fluid and cutting parameters must be properly selected. However, since the process dynamics is particular for each grinding process, especially in complex geometries, specific studies in real manufacturing conditions are required to understand the phenomena and minimize surface damages. In this context, this work aims to evaluate the surface integrity of M3 HSS cutting taps after they have been ground at various cutting conditions. Machining tests were performed in situ under controlled and variable wheel speed, depth of cut, and workpiece speed conditions. Machined surface images and microhardness below the surface were the output variables investigated. Results showed that, on average, the thickness of the affected surface layer was about 70% lower after machining at the lowest workpiece speed used. The correlation between grinding removal rates and thermal damage was also discussed.
Keywords: Grinding; Surface integrity; Thermal damage; HSS